Antiscaling 3D printed feed spacers via facile nanoparticle coating for membrane distillation. (1st February 2021) - Thomas, Navya; Kumar, Mahendra; Palmisano, Giovanni; Al-Rub, Rashid K. Abu; Alnuaimi, Reham Y.; Alhseinat, Emad; Rowshan, Reza; Arafat, Hassan A.
Highlights: Surface modification of 3D printed feed spacers was studied for scaling control in MD. FS nanoparticles coating on spacer favorably altered the latter's surface chemistry. Increased hydrophobicity and reduced SFE are the main mechanisms of performance. Scaling reduced by 74% and 60% on the spacer and the membrane, respectively. Abstract: Surface modification of feed spacers rather than membranes may hold more merit as an antiscaling strategy in membrane distillation (MD), as it avoids compromising the functionality of MD membrane. In this work, an antiscaling polyamide 3D printed spacer was developed for MD. The surface of the printed spacer was coated with fluorinated silica (FS) nanoparticles synthesized via a sol-gel process. The sol-gel approach used to synthesize the FS nanoparticles is considered a convenient and easy approach for engineering the spacer's surface structure and roughness. The performance of the FS coated printed surface was evaluated against other coating materials of different chemical properties. The coated surfaces were characterized using water contact angle measurements, ATR-FTIR, Raman, FESEM-EDX, atomic force and 3D microscopes. The 3D printed surface's microscale roughness and hydrophobicity increased, while its surface-free energy decreased with FS nanoparticles coating. The antiscaling performance of uncoated and FS coated spacers was then assessed in a direct contact MD process, using a scale-inducing aqueous solution of calcium sulfate as its feed. The scalant (Ca 2+ ) attachment on the FS coated spacer was 0.24 mg cm −2, 74% lower than on the uncoated 3D spacer (0.95 mg cm −2 ). Also, by using the antiscaling FS coated spacer, scaling on the membrane surface dropped by 60%. The predominant factors that helped minimize scaling with FS coating were microscale roughness-induced hydrophobicity and reduced surface-free energy that weakened the scalant 's interaction with the spacer surface. Graphical abstract: Image, graphical abstract